2015
DOI: 10.1007/s11284-015-1309-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in vegetation and nitrogen mineralization during recovery of a montane subtropical broadleaved forest in North‐eastern India following anthropogenic disturbance

Abstract: Understanding the changes in the plant community and soil nitrogen (N) availability during natural recovery of a forest following clear‐cutting is critical to develop post‐disturbance forest management strategies. Therefore, post‐clearcut changes in vegetation, net N mineralization rates and available N concentrations in soil were studied in a montane subtropical broadleaved forest during the early years of recovery following a chronosequence approach. Two replicate stands were selected for each treatment of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 58 publications
4
4
0
Order By: Relevance
“…The recovery of the N cycle with increasing stand age following disturbance showed a pattern similar to that seen in many other tropical forests [14,51,52], albeit not all [53], with increases in soil mineral N concentrations along with increased N-mineralization rates during succession. The increasing dominance in NH 4 -N over NO 3 -N with older stand age reflects a change in N cycling through the loss or rapid uptake of NO 3 -N in initial successional stages followed by accumulation of NH 4 -N in later successional stages leading to a "tighter" N cycle.…”
Section: Discussionsupporting
confidence: 63%
“…The recovery of the N cycle with increasing stand age following disturbance showed a pattern similar to that seen in many other tropical forests [14,51,52], albeit not all [53], with increases in soil mineral N concentrations along with increased N-mineralization rates during succession. The increasing dominance in NH 4 -N over NO 3 -N with older stand age reflects a change in N cycling through the loss or rapid uptake of NO 3 -N in initial successional stages followed by accumulation of NH 4 -N in later successional stages leading to a "tighter" N cycle.…”
Section: Discussionsupporting
confidence: 63%
“…The subtropical broad-leaved wet hill forests of Meghalaya are highly diverse, and part of the Indo-Burma biodiversity hotspot, which is primarily dominated by broad-leaved oak-laurel forests [37][38][39][40]. Various studies have been conducted in these forests to study species diversity, composition and structure [37,[39][40][41], natural regeneration [42][43][44], nutrient dynamics [45,46], and litter decomposition [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…On these degraded sites, a large portion of the topsoil has been eroded in this region of very heavy rainfall (averaging >11,000 mm a year). The remaining soil is shallow, nutrient-poor and acidic, and has low mechanical stability [46,52]. Consequently, forests in the region that once provided continuous cover, today, are fragmented into small remnant patches (Figure 1), which are often in a degraded state [46,53].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous previous studies and practices have shown that seasonal changes in N mineralization result in patterns with the highest mineralization rates in the summer and the lowest rates in the winter, which appears to follow seasonal patterns of temperature and precipitation [8][9][10][11]. Soil temperature, moisture, and precipitation patterns are important drivers of soil N transformations, and each of these seasonal climate conditions may have different impacts on various forest types [12]. Forest types with varying plant communities may have different influences on the N cycle due to differences in the physiology, morphology, nutrient requirements, and life histories of various plant species [13][14][15].…”
Section: Introductionmentioning
confidence: 99%